Cross-National Differences in Disability Among Elders: Transitions in Disability in Mexico and the United States - Gerst-Emerson, Kerstin (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES. Little is known about how exposure to a combination of infectious and chronic conditions throughout the lifecourse could impact disability in old age. This paper compares 2 cohorts of adults who have aged under very different country contexts by contrasting disability transitions among elders in Mexico with elders in the United States. METHODS. Data comes from the Mexican Health and Aging Study (MHAS) and the U.S. Health and Retirement Study (HRS). Estimated probabilities of 2-year transitions among disability states and mortality are presented for adults aged 50 and older. RESULTS. The levels of disability prevalence and 2 year transitions are consistent with a higher rate of disability for the United States compared to Mexico. In 2-year transitions, the U.S. sample was more likely to transition to a disabled state or increase the number of disabilities than the Mexican counterparts, while Mexicans are more likely to move out of disability or reduce the number of disabilities reported. DISCUSSION. The findings suggest that the current rate of disability in old age is lower for a less developed country compared with a developed society. We discuss implications, possible explanations, and likely future scenarios.